Perioperative serum inflammatory response and the development of atrial fibrilation after coronary artery bypass surgery - BENNETT, KATHLEEN; CREAN, PETER; KELLEHER, DERMOT P (BMJ, 2005)
Atrial fibrillation (AF) remains the most common cardiac arrhythmia and is associated with an increase in both morbidity and mortality. Some data in both the surgical and non-surgical settings suggest that inflammation has a pivotal role in the onset and propagation of AF. As on pump coronary artery bypass surgery is associated with a significant inflammatory response and an incidence of AF between 11?40%, we decided to use this model to study if there was a potential association between perioperative response and the development of postoperative AF.1,2
PUBLISHED
Keywords: adhesion molecules, atrial fibrillation, C reactive protein, coronary artery bypass surgery, inflammation